Against carceral data collection in response to anti-Asian violences. Issue 1 (June 2021) - Kuo, Rachel; Bui, Matthew
This commentary reflects on recent instances of anti-Asian violence and state responses to redress violence through data-driven strategies. Data collection often presents itself as an appealing strategy, due to impacted communities' desires for evidence and metrics to substantiate political claims. Yet, data collection can bolster the carceral state. This commentary takes an antagonistic approach to policing, including the ongoing creation of data infrastructures by—and for—law enforcement through hate crimes legislation. We critically discuss the challenges and possibilities in building towards anti-carceral responses amidst ongoing racial violence and crisis.